PERAN PEMERINTAH KOTA MEDAN DALAM MENCIPTAKAN PERSAINGAN USAHA YANG SEHAT DALAM PENETAPAN TARIF TAKSI ONLINE (STUDI PADA PEMERINTAH KOTA MEDAN) - Eka Suryani Giawa; Lazio Afriando Bukit; Sukses Marhasak Panungkunan Siburian; Agus Irawan (Ensiklopedia Education Review, 2023)
In today's all-digital era, people need technological sophistication that can make it easier for them in terms of transportation. Both the transportation of goods and public transportation that can expedite the work and activities that will be carried out by the community.Various kinds of transportation services have been prepared by business actors, such as Go-Car and Grab-Car which provide very easy transportation.With the difference in rates between online taxis and conventional taxis, in this case it is hoped that the Medan City Government will be able to resolve the fare problem between online taxis and conventional taxis so that no party feels disadvantaged. This study aims to analyze the Role Of The Government In Creating Fair Business Competition In Determining Online Taxi Rates (Study On Medan City Government).